TINGKAT KEPUASAN DAN LOYALITAS KONSUMEN TERHADAP CINCAU HITAM TGR DI BANDAR LAMPUNG - Rafif Tegar Shifano; Teguh Endaryanto; Yaktiworo Indriani (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2026)
TGR black grass jelly agroindustry is a black grass jelly producer facing a decline in selling, so understanding buyer satisfaction and loyalty is an important aspect of the sustainability of this business.  This study aimed to analyze the level of satisfaction and loyalty of consumer of TGR black jelly.  This study conducted at TGR black grass jelly agroindustriy in Bandar Lampung, and used a case study method.  The data gathered by interviewing 38 respondents consisting of 18 reseller agents and 20 household consumers.  The customer satisfaction index (CSI) and loyalty pyramid methods were applied to find out the level of consumer satisfaction and loyalty.  The results of this study revealed that the level of satisfaction of TGR black grass jelly buyers obtained a value of 70.78 percent, which meant that buyers were satisfied with TGR black jelly products, however about  29.22 percent of buyer expectations have not been achieved, while the level of loyalty of TGR black grass jelly buyers was categorized as loyal.      Key words:   Agent, black grass jelly, buyer, loyaly, satisfaction